Analisis Pendapatan Pengemudi Ojek Pangakalan di Pasar Mardika Kota Ambon - Asi, Karmila; Papilaya, Josef; Rehatta, Geradin (Universitas Pattimura, 2025)
Informal transportation such as motorcycle taxi stands at Mardika Market, Ambon City plays a crucial role in community mobility, yet the emergence of online transportation creates new challenges for drivers’ income. This study aims to analyze the income level of motorcycle taxi drivers and the factors influencing it. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation with ten drivers. Findings reveal that the average income ranges from IDR 2,050,000 to 3,700,000 with operational costs between IDR 550,000 and 950,000, alongside a decrease in passengers after the arrival of online platforms. Key factors affecting income include working hours, fares, and ownership of side jobs. The study highlights how drivers sustain their livelihoods through adaptive strategies despite intense competition with app-based services. These results enrich the discourse on the sustainability of informal labor while providing insights for local governments and transport associations to design supportive policies.